2008
DOI: 10.1007/s00426-008-0171-5
|View full text |Cite
|
Sign up to set email alerts
|

Semantic processing of crowded stimuli?

Abstract: Effects of semantic processing of crowded characters were investigated using numbers as stimuli. In an identification task, typical spacing effects in crowding were replicated. Using the same stimuli in a magnitude comparison task, a smaller effect of spacing was observed as well as an effect of response congruency. These effects were replicated in a second experiment with varying stimulus-onset asynchronies. In addition, decreasing performance with increasing onset-asynchrony (so-called type-B masking) for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
3
16
0
Order By: Relevance
“…In line with the results of Bahrami et al (2010), a robust impact of non-consciously perceived numerical information has been demonstrated in healthy participants with a variety of techniques beyond CFS, such as crowding (Huckauf, Knops, Nuerk, & Willmes, 2008) and masking (Dehaene et al, 1998;Naccache & Dehaene, 2001), as well as in patients suffering from hemineglect (Sackur et al, 2008). These results were taken as evidence for an elaborate processing of non-consciously presented numerical information.…”
Section: Unconscious Numerical Priming With Other Techniquessupporting
confidence: 77%
“…In line with the results of Bahrami et al (2010), a robust impact of non-consciously perceived numerical information has been demonstrated in healthy participants with a variety of techniques beyond CFS, such as crowding (Huckauf, Knops, Nuerk, & Willmes, 2008) and masking (Dehaene et al, 1998;Naccache & Dehaene, 2001), as well as in patients suffering from hemineglect (Sackur et al, 2008). These results were taken as evidence for an elaborate processing of non-consciously presented numerical information.…”
Section: Unconscious Numerical Priming With Other Techniquessupporting
confidence: 77%
“…Note that an account of a high-level mechanism for the crowding effect does not presuppose sequential processing whereby identification is followed by semantic extraction; the two processes may rely, as we have suggested, on different neural circuits. A recent study by Huckauf et al (2008) showed that crowded stimuli can give rise to semantic activation, but the researchers found semantic activation only for stimuli that were consciously identified. To our knowledge, our study is the first to demonstrate robust semantic activation for word primes that are so severely crowded that they cannot be consciously identified.…”
Section: Discussionmentioning
confidence: 96%
“…For example, given a crowded display ‘BTH’, an observer may respond ‘BHT’. Clearly some information about the target is preserved (perhaps even semantic information [40]), but the location information is lost.…”
Section: What Information Survives Crowding?mentioning
confidence: 99%